True oxygen reduction capacity during photosynthetic electron transfer in thylakoids and intact leaves - Fitzpatrick Duncan; Aro Eva-Mari; Tiwari Arjun (OXFORD UNIV PRESS INC, 2022)
Photosynthetically derived H2O2 only accumulates at Photosystem I and may trigger cooperation with mitochondria during stress.Reactive oxygen species (ROS) are generated in electron transport processes of living organisms in oxygenic environments. Chloroplasts are plant bioenergetics hubs where imbalances between photosynthetic inputs and outputs drive ROS generation upon changing environmental conditions. Plants have harnessed various site-specific thylakoid membrane ROS products into environmental sensory signals. Our current understanding of ROS production in thylakoids suggests that oxygen (O-2) reduction takes place at numerous components of the photosynthetic electron transfer chain (PETC). To refine models of site-specific O-2 reduction capacity of various PETC components in isolated thylakoids of Arabidopsis thaliana, we quantified the stoichiometry of oxygen production and consumption reactions associated with hydrogen peroxide (H2O2) accumulation using membrane inlet mass spectrometry and specific inhibitors. Combined with P700 spectroscopy and electron paramagnetic resonance spin trapping, we demonstrate that electron flow to photosystem I (PSI) is essential for H2O2 accumulation during the photosynthetic linear electron transport process. Further leaf disc measurements provided clues that H2O2 from PETC has a potential of increasing mitochondrial respiration and CO2 release. Based on gas exchange analyses in control, site-specific inhibitor-, methyl viologen-, and catalase-treated thylakoids, we provide compelling evidence of no contribution of plastoquinone pool or cytochrome b6f to chloroplastic H2O2 accumulation. The putative production of H2O2 in any PETC location other than PSI is rapidly quenched and therefore cannot function in H2O2 translocation to another cellular location or in signaling.